(untitled) (Journal of Educational Sciences, 2020)
Didactic goal setting is the most important regulatory part of the activity of each teacher and each education manager. It is a daily duty and an indicator of professional pedagogical competence. In order to determine the main directions of activities of the lyceum’s management team in the area of improving the competence of teachers in didactic goal setting, we have studied the learning objectives that teachers of the lyceum put in their practice of project lessons. The goals formulated by the teachers and fixed in the plans are analyzed, firstly, from the position of the implemented pedagogical approaches to the definition of goals; secondly, from the position of the level of the projected cognitive activity of students in accordance with B. Bloom’s taxonomy. This made it possible to identify the real difficulties of teachers in the field of goal-setting and to outline the directions of actions of the lyceum’s management team in raising the competence of teachers in goal-setting educational activities of lyceum students. The aims set by 30 teachers of disciplines of natural-mathematical cycle and 20 teachers of subjects of social and humanitarian direction were analyzed. The study was made according to the Methodology of Action Research, which involves turning to practical experience as an object of own research of the subject in order to move towards effective teaching and translation of successful pedagogical solutions. In the course of the work, classical methods of analyzing scientific literature were used; study of the products of teachers and methodologists, school documentation. Key words: the purpose of training, didactic goal setting, professional and pedagogical competence, teacher competence in didactic goal setting.